2022
DOI: 10.31348/2022/26
|View full text |Cite
|
Sign up to set email alerts
|

Chelation of Band Keratopathy in Long-Term Observation

Abstract: Aim: To report the clinical results of chelation of band keratopathy in long-term follow-up. Material and methods: The long-term results of 5 patients (5 eyes) with symptomatic band keratopathy with a follow-up period of at least 6 months, in whom 2% EDTA was chelated on the affected eye in the study period from April 2018 to March 2021, were retrospectively evaluated. The follow-up period was 9-37 months. Results: In all patients, there was a significant improvement in the local findings and an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…DISCUSSION Band keratopathy is a chronic degenerative corneal disease which is often caused by calcium deposition in the Bowman's layer [1] , as also named calcific band keratopathy (CBK). CBK often occurs secondary to systemic or ocular diseases such as uveitis, hyperparathyroidism, and hypercalcemia due to chronic kidney disease [2][3][4] . The early lesions originate from the peripheral cornea.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Band keratopathy is a chronic degenerative corneal disease which is often caused by calcium deposition in the Bowman's layer [1] , as also named calcific band keratopathy (CBK). CBK often occurs secondary to systemic or ocular diseases such as uveitis, hyperparathyroidism, and hypercalcemia due to chronic kidney disease [2][3][4] . The early lesions originate from the peripheral cornea.…”
Section: Case Presentationmentioning
confidence: 99%
“…However, for CBK, the concentration is usually between 3% and 5% [10] . Most patients experience a certain degree of visual improvement after EDTA chelation therapy, and it can also alleviates patient discomfort [3,5,9,11] . Furthermore, studies have shown that EDTA has minimal cytotoxicity to corneal cells and, under certain conditions, can promote cell growth [12] .…”
Section: Edta Solution For Band Keratopathymentioning
confidence: 99%